2020
DOI: 10.1158/1078-0432.ccr-19-2803
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Chemokine Signature Is Associated with a T-cell–Inflamed Phenotype in Primary and Metastatic Pancreatic Cancer

Abstract: ◥Purpose: The molecular drivers of antitumor immunity in pancreatic ductal adenocarcinoma (PDAC) are poorly understood, posing a major obstacle for the identification of patients potentially amenable for immune-checkpoint blockade or other novel strategies. Here, we explore the association of chemokine expression with effector T-cell infiltration in PDAC.Experimental Design: Discovery cohorts comprised 113 primary resected PDAC and 107 PDAC liver metastases. Validation cohorts comprised 182 PDAC from The Cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 82 publications
6
73
0
Order By: Relevance
“…Furthermore, the expression of phagocytosis checkpoint, SIRPa, was lower in the m6Ascore-high group, which may contribute to immune evasion. A chemokine signature which consists of four chemokines (CCL4, CCL5, CXCL9 and CXCL10) was reported to be associated with CD8+ T cells infiltration in PDAC [32]. The current study also found that m6Ascore-low tumors are characterized with increased profiles of CCL and CXCL chemokine ligands, similar to the "T cell-inflamed" phenotype proposed by Romero and colleagues, which may partially explain the distinct immune infiltration profiles between m6Ascore-low and m6Ascore-high tumors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the expression of phagocytosis checkpoint, SIRPa, was lower in the m6Ascore-high group, which may contribute to immune evasion. A chemokine signature which consists of four chemokines (CCL4, CCL5, CXCL9 and CXCL10) was reported to be associated with CD8+ T cells infiltration in PDAC [32]. The current study also found that m6Ascore-low tumors are characterized with increased profiles of CCL and CXCL chemokine ligands, similar to the "T cell-inflamed" phenotype proposed by Romero and colleagues, which may partially explain the distinct immune infiltration profiles between m6Ascore-low and m6Ascore-high tumors.…”
Section: Discussionsupporting
confidence: 84%
“…The results above indicate m6Ascore is correlated to tumor immune evasion. We investigated the expression of ligands and receptors in Chemokine Ligand (CCL) and chemokine (C-X-C motif) ligand (CXCL) chemokine family, which has been reported to regulate CD8+ T cells infiltration in PDAC [32], and found that most ligands and receptors in CCL and CXCL family decreased in m6Ascore-high tumors, including CCL4 and CCL5 (Fig. 8a).…”
Section: Gene Set Enrichment Analysis (Gsea) Identified Activated Andmentioning
confidence: 99%
“…CCL2 is required for tumor-associated macrophages to induce immune evasion (26), to promote cancer cell progression (27) and invasion (28). Furthermore, CCL4 is associated with a T cell-inflamed phenotype in primary and metastatic pancreatic cancer (29). Therefore, B3GNT3, as a potential unfavorable prognostic maker, might contribute to the low infiltration of immune cells and immunostimulators.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the tumor immune response level in clinical tissue samples, we examined CYT [26,27], calculated as the geometric mean of GZMA and PRF1 expression values, since both molecules are tightly co-expressed in TCGA samples [19]. GZMA and PRF1 are dramatically upregulated upon CD8+ T cell activation [28].…”
Section: Evaluation Of Cytolytic Activity (Cyt) and Tumor-infiltrating Lymphocyterelated Moleculesmentioning
confidence: 99%